Multiple truly topological unidirectional surface magnetoplasmons at terahertz frequencies - S. Fan; T. Guo; B. Zhou; J. Xu; Deng, X.; J. Lei; Shen, Y.; M. Fu; K. L. Tsakmakidis; L. Hong (Phys. Rev. B, 2025)
Unidirectional propagation based on surface magnetoplasmons (SMPs) has recently been realized at the interface of magnetized semiconductors. However, usually SMPs lose their unidirectionality due to nonlocal effects, especially in the lower trivial band gap of such structures. More recently, a truly unidirectional SMP (USMP)hasbeen demonstrated in the upper topological nontrivial band gap, but it supports only a single USMP, limiting its functionality. In this work, we present a fundamental physical model for multiple, robust, truly topological USMP modes at terahertz (THz) frequencies, realized in a semiconductor-dielectric-semiconductor (SDS) slab waveguide under opposing external magnetic fields. We analytically derive the dispersion properties of the SMPs and perform numerical analysis in both local and nonlocal models. Our results show that the SDS waveguide supports two truly (even and odd) USMP modes in the upper topological nontrivial band gap. Exploiting these two modes, we demonstrate unidirectional SMP multimode interference (USMMI), being highly robust and immune to backscattering, overcoming the back-reflection issue in conventional bidirectional waveguides. To demonstrate the usefulness of this approach, we numerically realize a frequency and magneti cally tunable arbitrary-ratio splitter based on this robust USMMI, enabling multimode conversion. We, further, identify a unique index-near-zero (INZ) odd USMP mode in the SDS waveguide, distinct from conventional semiconductor-dielectric-metal waveguides. Leveraging this INZ mode, we achieve phase modulation with a phase shift from −π to π. Our work expands the manipulation of topological waves and enriches the field of truly nonreciprocal topological physics for practical device applications.